Identification of QTL for Stem Traits in Wheat (Triticum aestivum L.) - Niu, Yanan; Chen, Tianxiao; Zhao, Chenchen; Guo, Ce; Zhou, Meixue (Frontiers in Plant Science, 2022)
Lodging in wheat (Triticum aestivum L.) is a complicated phenomenon that is influenced by physiological, genetics, and external factors. It causes a great yield loss and reduces grain quality and mechanical harvesting efficiency. Lodging resistance is contributed by various traits, including increased stem strength. The aim of this study was to map quantitative trait loci (QTL) controlling stem strength-related features using a doubled haploid (DH) population derived from a cross between Baiqimai and Neixiang 5. Field experiments were conducted during 2020-2022, and glasshouse experiments were conducted during 2021-2022. Significant genetic variations were observed for all measured traits, and they were all highly heritable. Fifteen QTL for stem strength-related traits were identified on chromosomes 2D, 3A, 3B, 3D, 4B, 5A, 6B, 7A, 7D, respectively, and 7 QTL for grain yield-related traits were identified on chromosomes 2B, 2D, 3D, 4B, 7A, 7B, respectively. The superior allele of the major QTL for the number of vascular bundles (VB) was independent of plant height (PH), making it possible to improve stem strength without a trade-off of PH thus improving lodging resistance. VB also showed positive correlations with some of the yield components. The result will be useful for molecular marker-assisted selection (MAS) for high stem strength and high yield potential.